Arvo Pärt - Mocanu, Daniel (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
Arvo Pärt’s music is a deeply religious music, in which any man endowed with that mystical sense can observe the soul of the composer in the balance, between the inner searches, with all the burns of the stages of spiritual growth and the living presence of the man carrying the Holy Spirit in the Church and in the world. Many things have been said and will be said about Arvo Pärt’s work, but what is fascinating about this message is the constant invitation to inner introspection. If we were to name it in any way, then we would call it the music of the search for the Holy Spirit.